Redefining Second Stage of Labor: Number of Pushing Contractions - Bok, Serin M.; Carmona, Gabriela E. Pena; Crawford, Jake; Eskander, Ramy; Desai, Mina; Ross, Michael G. (American Journal of Perinatology Reports, 2020)
Introduction Despite time standards for second stage labor, “delayed pushing,” uterine contraction frequency, and alternate contraction pushing may alter the effective maternal effort. We sought to quantify the number of pushing contractions needed for a spontaneous vaginal delivery (SVD) among primipara and multipara patients.Methods Deliveries at Harbor-UCLA Medical Center in 2017 were selected for SVD of singleton, term newborns. The first 100 primipara and 100 multipara deliveries were analyzed and monitor tracings quantified for pushing contractions.Results Significantly more pushing contractions were required by primiparas versus multiparas (17.3 ± 1.7 vs. 5.5 ± 0.7; p < 0.001) in accord with a longer second stage (86.7 ± 7.8 vs. 27.2 ± 4.9 min; p < 0.001) and epidural was associated with greater number of pushing contractions among both primipara (18.5 ± 1.8 vs. 10.8 ± 0.8) and multipara women (6.1 ± 0.8 vs. 4.1 ± 0.3). Newborn weight (<3000, 3000–3500, >3500 g) demonstrated a trend for increased pushing contractions among primipara (16.9, 16.5, 19.8 pushes, respectively) though not multiparas.Conclusion Although correlated with the absolute duration of the second stage, the number of pushing contractions eliminates ambiguities of “delayed pushing,” pushing every-other, and frequency of contractions. Examination of larger databases and patients with second stage “arrest disorders” may provide pushing contraction criteria predictive of SVD and prevention of morbidity.
Keywords: Labor; pushing; second stage; duration